Pengalaman pegawai mengelola cyber PR pada diskominfo kota Padang - Viona Putri Yarisda; Sarmiati Sarmiati; Elva Ronaning Roem (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
The background of this research was writer observation at Dinas Komunikasi dan Informasi (Diskominfo) in Padang. The result of observation showed that: still low Cyber PR controlling at there. The aim of this research was to know the experience of Communication Activities of Cyber PR Employees of Padang City Government carried out by Diskominfo in delivering information to the public. The informans of this research were 6 servants at Diskominfo Padang. The instrument of this research was interview and observation. The results of this research showed that four main stages or steps that become the basis of reference for the implementation of Cyber PR activities for Padang City Communication and Informatics employees as Public Relations, 1.Fact and problem finding stage, where the facts obtained in the field are based on current events, but there are constraints on the shortage of human resources and budget funds. 2.Planning stage, carried out by presenting information with frequent intensity. 3.The communication stage is carried out between the manager of each media and the head of the Cyber PR manager. 4.Evaluation stage, is carried out by paying attention to the insight of each media to measure the public's response.